CD8 (+) T-Cells Count in Acute Myocardial Infarction in HIV Disease in a Predominantly Male Cohort. - Badejo, Oluwatosin A; Chang, Chung-Chou; So-Armah, Kaku A; Tracy, Russell P; Baker, Jason V; Rimland, David; Butt, Adeel A; Gordon, Adam J; Rinaldo, Charles R; Kraemer, Kevin; Samet, Jeffrey H; Tindle, Hilary A; et al. (BioMed research international, 2015)
Human Immunodeficiency Virus- (HIV-) infected persons have a higher risk for acute myocardial infarction (AMI) than HIV-uninfected persons. Earlier studies suggest that HIV viral load, CD4(+) T-cell count, and antiretroviral therapy are associated with cardiovascular disease (CVD) risk. Whether CD8(+) T-cell count is associated with CVD risk is not clear. We investigated the association between CD8(+) T-cell count and incident AMI in a cohort of 73,398 people (of which 97.3% were men) enrolled in the U.S. Veterans Aging Cohort Study-Virtual Cohort (VACS-VC). Compared to uninfected people, HIV-infected people with high baseline CD8(+) T-cell counts (>1065 cells/mm(3)) had increased AMI risk (adjusted HR = 1.82, P < 0.001, 95% CI: 1.46 to 2.28). There was evidence that the effect of CD8(+) T-cell tertiles on AMI risk differed by CD4(+) T-cell level: compared to uninfected people, HIV-infected people with CD4(+) T-cell counts ≥200 cells/mm(3) had increased AMI risk with high CD8(+) T-cell count, while those with CD4(+) T-cell counts <200 cells/mm(3) had increased AMI risk with low CD8(+) T-cell count. CD8(+) T-cell counts may add additional AMI risk stratification information beyond that provided by CD4(+) T-cell counts alone.